Bridging science and heritage in the Balkans : studies in archaeometry and cultural heritage restoration and conservation - Palincaş, Nona; Ponta, C. C. (Archaeopress Publishing Ltd, 2019)
In a period when the study of archaeological remains is enriched through new methods derived from the natural sciences and when there is general agreement on the need for more investment in the study, restoration and conservation of the tangible cultural heritage, this work presents contributions to these fields from South-Eastern Europe.